Upaya Meningkatkan Minat Belajar Siswa Dengan Model Pembelajaran Problem Based Learning Pada Materi Kemampuanku Terbatas Kelas VII di SMPN 1 Sanaman Mantikei - Yohana Godelifa Nago (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Students' interest in learning is something that is important in the smooth teaching and learning process. Students who have high interest in learning in the learning process can support the teaching and learning process to improve, and vice versa, if students have low interest in learning, the quality of learning will decrease and this will affect learning outcomes. Slameto (1995: 57) explains that interest is